2014
DOI: 10.1371/journal.pone.0094905
|View full text |Cite
|
Sign up to set email alerts
|

RyR2 Modulates a Ca2+-Activated K+ Current in Mouse Cardiac Myocytes

Abstract: In cardiomyocytes, Ca2+ entry through voltage-dependent Ca2+ channels (VDCCs) binds to and activates RyR2 channels, resulting in subsequent Ca2+ release from the sarcoplasmic reticulum (SR) and cardiac contraction. Previous research has documented the molecular coupling of small-conductance Ca2+-activated K+ channels (SK channels) to VDCCs in mouse cardiac muscle. Little is known regarding the role of RyRs-sensitive Ca2+ release in the SK channels in cardiac muscle. In this study, using whole-cell patch clamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…10,38 We previously showed that RyR2 alters SK2 channel activity in cardiac myocytes due to changed in the intracellular Ca 2+ levels. 35 Our present results reveal that interfering RNA silencing of endogenous JP2 caused a significantly reduced density of I k,Ca. and reduced amplitude of the Ca 2+ transient in the mice cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…10,38 We previously showed that RyR2 alters SK2 channel activity in cardiac myocytes due to changed in the intracellular Ca 2+ levels. 35 Our present results reveal that interfering RNA silencing of endogenous JP2 caused a significantly reduced density of I k,Ca. and reduced amplitude of the Ca 2+ transient in the mice cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
“…In our previous study, we demonstrated co-immunoprecipitation of RyR2 and the SK2 channel in the heart. 35 Interestingly, we observed that JP2 was also immunoprecipitated with an antibody against RyR2 ( Figure 1C). Take together; these results indicate the specific interaction between JP2 and SK2 in native cardiac tissue.…”
Section: Jp2 Associates With Sk2 Channel In Native Cardiac Tissuementioning
confidence: 85%
See 1 more Smart Citation
“…29 In parallel, Mu et al showed that RyR2-mediated SR Ca 2+ release is at least in part responsible for activation of atrial plasmalemmal SKs. 30 Colocalization of SKCa channels with voltage-dependent Ca 2+ channels points to their involvement in repolarization of the action potential. However, responsiveness of SKs to SR Ca 2+ release suggests that they can play an additional important role counteracting the depolarizing force of the Na + /Ca 2+ exchanger.…”
Section: Structure/functionmentioning
confidence: 99%
“…The co-localization of SK and Ca 2+ channels suggests the possibility that local subsarcolemmal Ca 2+ resulting from opening of Ca 2+ channels is sufficient to activate SK channels as was demonstrated for hippocampal neurons 46 . However, two recent studies suggested that sarcoplasmic reticulum (SR) Ca 2+ release is required for the activation of cardiac SK channels 47,48 . One of these studies utilized over-expressed SK channels and the regulation of the over-expressed SK channels maybe distinct compared to native cardiomyocytes.…”
Section: Cardiac Sk Channel Interactomementioning
confidence: 99%